2012
DOI: 10.1073/pnas.1200764109
|View full text |Cite
|
Sign up to set email alerts
|

Saposins utilize two strategies for lipid transfer and CD1 antigen presentation

Abstract: Transferring lipid antigens from membranes into CD1 antigenpresenting proteins represents a major molecular hurdle necessary for T-cell recognition. Saposins facilitate this process, but the mechanisms used are not well understood. We found that saposin B forms soluble saposin protein-lipid complexes detected by native gel electrophoresis that can directly load CD1 proteins. Because saposin B must bind lipids directly to function, we found it could not accommodate long acyl chain containing lipids. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…Together, these results highlight the important role of saposins as lipid-editors for CD1d antigen presentation, in addition to GM2a (9) and Niemann Pick type C2 protein (NPC2) (58). In contrast to DM molecules, which edit the repertoire of peptides bound to MHC class II molecules (59), saposins do not have an enzymatic mechanism of action and we and others have not been able to demonstrate physical association with human CD1d molecules (8), unlike what has been shown for murine CD1d and saposin A (9) or human CD1b and CD1c and saposin C (7,11). Despite extensive in vivo and in vitro studies, the ultimate mechanism of hydrolase activation by saposins is unclear and that of lipid transfer onto CD1d molecules remains unknown.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Together, these results highlight the important role of saposins as lipid-editors for CD1d antigen presentation, in addition to GM2a (9) and Niemann Pick type C2 protein (NPC2) (58). In contrast to DM molecules, which edit the repertoire of peptides bound to MHC class II molecules (59), saposins do not have an enzymatic mechanism of action and we and others have not been able to demonstrate physical association with human CD1d molecules (8), unlike what has been shown for murine CD1d and saposin A (9) or human CD1b and CD1c and saposin C (7,11). Despite extensive in vivo and in vitro studies, the ultimate mechanism of hydrolase activation by saposins is unclear and that of lipid transfer onto CD1d molecules remains unknown.…”
Section: Discussionmentioning
confidence: 74%
“…Despite high homology, the four saposins have different lipid specificities, as demonstrated by the phenotype of patients with selective deficiency of individual molecules (53). We limited our study to the role of saposin B, because evidence from our own works and from the literature (8,11,32) suggested its dominant role in loading soluble lipids onto CD1d molecules. We determined the binding affinity of saposin B to a radiolabeled version of ThrCer at pH5 and pH7 (1.8 μM and 4.5 μM, respectively), and observed that it reached a plateau when saposin B was present in molar excess.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Sap-C was completely ineffective in this in vitro digestion assay. Recent studies comparing the mode of action of Sap-B and Sap-C showed that the two investigated saposins use different strategies for structurally diverse lipid antigen presentation (24). Although Sap-B forms soluble saposin-lipid complexes and can directly load CD1 proteins, Sap-C inserts itself directly into the membrane bilayer, thereby disrupting the tightly packed lipid bilayer and thus facilitating antigen loading onto the presenting CD1 protein.…”
Section: Discussionmentioning
confidence: 99%